Disparity in Police Disciplinary Outcomes: The Mediating Effect of Complaint Disposition for Organizational Outgroups - Jill Nicholson-Crotty; Courtney Hahm; Sean Nicholson-Crotty (The American Review of Public Administration, 2026)
In response to demands for greater police accountability, many departments have adopted policies designed to better regulate the use of force and to make it easier to investigate and punish officers accused of wrongdoing. While not widespread, there is some evidence that these changes have increased disciplinary actions. However, it remains uncertain whether police discipline has been applied equitably across racial and gender groups within departments. Drawing on multiple bodies of scholarship, we develop the expectation that, because of their status as members of organizational outgroups, Black, Hispanic and female officers are likely to be disciplined at higher rates. Importantly, we also argue that racial, ethnic and gender differences in disciplinary outcomes are at least partially mediated by the way in which police departments treat complaints against these officers. We test these hypotheses in data from Chicago's Civilian Office of Police Accountability (COPA) from 1971 through 2018. Analyses of over 249,000 allegations indicate that female and Black officers and officers face a higher likelihood of reprimand and suspension compared to White male officers. Differences across these groups are entirely explained, however, by the greater likelihood that complaints against these officers are deemed sufficiently supported by evidence to warrant disciplinary action. We conclude by discussing the broader implications for understanding employee discipline and the potential impact of recent efforts to enhance police accountability.